THE PROBLEM OF FORMING «SOFT SKILLS» AMONG STUDENTS OF THE EDUCATIONAL PROGRAM «PEDAGOGY AND PSYCHOLOGY» - Алимкул, Айжан; Aizhanova, Gulnar (Pedagogy and Psychology, 2022)
The article is devoted to the problem of the formation of flexible or soft competences in the process of mastering the disciplines of the educational program “Pedagogy and Psychology”. Lock down in 2020 clearly demonstrated the need for the development and formation of soft skills in students, which make it possible to find a way to adapt in the face of a ban on one or another activity, while not losing productivity and competitiveness. The success of these complex tasks is almost entirely determined by the development of graduates’ soft skills. Soft skills in the context of world experience are well represented in various foreign publications. In this work, the authors made a brief analytical review of the current educational program of the bachelor’s degree “Pedagogy and Psychology” on the basis of the Kazakh National University named after Abai. The article shows the features of the formation of soft skills in a pedagogical university. The possibilities of the educational process and pedagogical conditions for the effective formation of soft skills (soft skills) are revealed. Key words: Soft Skills, flexible skills, Hard Skills, educational program "Pedagogy and Psychology", students.